Multi-phase coronary magnetic resonance angiography improves delineation of coronary arteries. (November 2019) - Zitzelsberger, Tanja; Krumm, Patrick; Hornung, Andreas; Kramer, Ulrich; Nikolaou, Konstantin; Schäfer, Jürgen F; Schick, Fritz; Sieverding, Ludger; Martirosian, Petros
Abstract: Background: Coronary artery magnetic resonance angiography (CMRA) is a robust tool for delineation of the coronary artery anatomy. In order to overcome the issue of visual delineation of the quietest heart phase, we implemented a new three-dimensional (3D) multi-phase whole-heart CMRA. Purpose: To evaluate the 3D multi-phase whole-heart CMRA technique for depiction of the coronary arteries and simultaneous assessment of cardiac function. Material and Methods: Ten healthy volunteers were included in a prospective study comprising 3D whole-heart CMRA with multiple-phase acquisition on 1.5-T MR. As a reference for coronary artery imaging, single-phase CMRA was performed. Furthermore, two-dimensional SSFP imaging was performed for functional assessment. Vessel sharpness (VS) was rated on a 5-point Likert scale (5 = best) and ventricular volumes were assessed in respective sequences. Results: VS scores were rated higher in multi-phase compared to single-phase CMRA: mean VS of the RCA was 4.6 ± 0.52 in multi-phase and 3.6 ± 1.17 in single-phase CMRA (z = –2.232, P  = 0.031). Mean VS of the LM was 4.2 ± 0.79 vs. 3.7 ± 0.82 (z = –2.236, P  = 0.063), of the LCX was 3.8 ± 1.03 vs. 3.4 ± 1.01 (z = –1.265, P  = 0.359), and of the LAD was 3.9 ± 0.59 vs. 3.9 ± 0.32 (z = 0, P  = 1.00). In functional assessment, the mean difference between multi-phase CMRA and two-dimensional SSFP imaging for assessing the end-diastolic volume of the left ventricle (LV-EDV) was –0.38% (95% CI -2.41–1.64) and for the right ventricular EDV –0.28 (95% CI -3.51–2.96). Conclusion: The 3D multi-phase CMRA approach allows a time efficient depiction of the coronary arteries and a coeval functional assessment, with an improved vessel sharpness of the coronaries.